2014
DOI: 10.17492/focus.v1i1.2476
|View full text |Cite
|
Sign up to set email alerts
|

OFDI between India and the Latin American Region - A Firm Level Motive Analysis

Abstract: India and the Latin America and Caribbean (LAC) region have emerged as major growth drivers of the world economy in the last couple of decades. Trade and investment relations between these regions have traditionally been rather insignificant but have picked up in recent years. Since 2000, Indian companies have invested about $12 billion in the LAC region across various industries. This paper examines the important issue of the motives driving OFDI between the two regions. It uses content analysis to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Market size has been one of the most significant macroeconomic determinants of M&As. A number of studies have found market size to have a positive impact on M&A (Boateng et al, 2011; Malhotra et al, 2011; Pradhan, 2010; Uddin & Boateng, 2010; Varma & Nayyar, 2015) This is consistent with the logic that large size of market gives opportunity for a company to generate more revenue and profit and hence, provides the incentive to invest in that market. Since the IT sector has a positive spillover effect on the growth of the rest of the domestic economy (Addison & Heshmati, 2003) and IT products and applications increase the productivity and efficiency of companies of other sectors, the revenue of IT companies also depends on the growth of other sectors, and the latter depends on the size of the market.…”
Section: Developing Research Hypothesessupporting
confidence: 62%
See 4 more Smart Citations
“…Market size has been one of the most significant macroeconomic determinants of M&As. A number of studies have found market size to have a positive impact on M&A (Boateng et al, 2011; Malhotra et al, 2011; Pradhan, 2010; Uddin & Boateng, 2010; Varma & Nayyar, 2015) This is consistent with the logic that large size of market gives opportunity for a company to generate more revenue and profit and hence, provides the incentive to invest in that market. Since the IT sector has a positive spillover effect on the growth of the rest of the domestic economy (Addison & Heshmati, 2003) and IT products and applications increase the productivity and efficiency of companies of other sectors, the revenue of IT companies also depends on the growth of other sectors, and the latter depends on the size of the market.…”
Section: Developing Research Hypothesessupporting
confidence: 62%
“…However, “corruption” and “regulatory inefficiency” were found to affect FDI inflows positively. Other studies such as Du and Boateng (2012), Varma and Nayyar (2015) and Iarossi (2009) have also examined similar dimensions and found macroeconomic determinants to be significantly affecting M&As.…”
Section: Building On Prior Researchmentioning
confidence: 80%
See 3 more Smart Citations